2021
DOI: 10.2147/dddt.s323107
|View full text |Cite
|
Sign up to set email alerts
|

Umbilical Cord Mesenchymal Stem Cell Therapy for Regenerative Treatment of Rheumatoid Arthritis: Opportunities and Challenges

Abstract: Rheumatoid arthritis (RA) is an autoimmune disease of unknown etiology with a high rate of disability. Traditional treatments for RA remain a challenging issue. For example, nonsteroidal anti-inflammatory drugs (NSAIDs) have no therapeutic effects on joint destruction, and the prominent side effects include gastrointestinal symptoms. RA is characterized by recurrence and bone attrition. Therefore, regenerative medicine and the use of umbilical cord mesenchymal stem cell (UC-MSC) therapies have recently emerged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 63 publications
(82 reference statements)
1
23
0
Order By: Relevance
“…In this study, they presented two particularly extraordinary clinical outcomes of two patients, who experienced remission nearly 6 months post-treatment, and have since maintained these positive effects, which enables them free movement and a life free of pain, joint swelling, and deformity [ 40 ]. The same group, provide evidence that UC-MSCs based therapy seem to be efficient and safe to be used in clinical practice [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, they presented two particularly extraordinary clinical outcomes of two patients, who experienced remission nearly 6 months post-treatment, and have since maintained these positive effects, which enables them free movement and a life free of pain, joint swelling, and deformity [ 40 ]. The same group, provide evidence that UC-MSCs based therapy seem to be efficient and safe to be used in clinical practice [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Currently, stem cell-based therapies are one of the most important emerging medical fields indifferent pathophysiological conditions and diseases, such as cardio-vascular diseases [ 26 , 27 , 28 ], autoimmune diseases [ 29 , 30 ], hereditary genetic conditions [ 31 ], and cancer [ 32 , 33 ]. Mesenchymal stem cells have attracted an increased attention as cellular vehicles for cancer therapy due to their low immunogenicity, fast ex vivo expansion, and inherent tumor-tropism and migratory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, dozens of clinical trials on MSCs for RA have been conducted (Table 2) based on the evidence that they can regulate the immune response, stimulate injury repair, and reduce the inflammatory response, as shown in preclinical studies. [97] The first pilot study of MSCs in RA was reported in 2011. [98] Three patients were infused IV with autologous…”
Section: Rheumatoid Arthritismentioning
confidence: 99%